Crystal structure of heterodonor ligands with their potential application - How, Fiona Ni Foong; Rahima, Z. A.; Amalina, M.S; Abdul Halim, S. Nadiah; Khaledi, Hamid (2012)
In pursuing application potential-based compounds,heteroatom donor ligands were specifically designed,synthesized and characterized with single-crystal X-ray diffraction that is a non-destructive analytical technique that provides very detailed information about theinternallatticeofcrystallinesubstancesofthesesynthesizd ligands.Dipotassium disulfanilamidate trihydrate is expected to exhibit significant biological activity as it possess the core structure of sulfanilamide with the ionic characteristic that enable it to influence the current fluctuations in cell membrane.4-Hydroxy-3-methoxybenzaldehyde–nicotinamide(1/1)with its cocrystal structures exhibit long-range order with hydrogen bonding and pi-pi interactions.These intermolecular interactions generate physical and chemical properties that are different from the properties of the parent compounds that would benefit the crystal engineering and in pharmaceutical industry.4,4'-[(1E,2E)-hydrazine-1,2-diylidenedi(E)methylylidene]bis(2-methoxyphenol)are hydrazones that can bind to metal ions to form complexes that are expected to possess different geometries and propertiesthat are worthwhile to inestigate.They are known to possess biological properties,electrochemical properties,fluorescence properties,nonlinear optical properties(NLO)and polymeric properties.